Association of the ANXA9 gene with milk production and its components in Awassi sheep - Almaamory, Yasseen A.; Al-Anbari, N.N. (Journal of Kerbala for Agricultural Sciences, 2023)
The study was conducted in the sheep farm of the Al-Fayhaa station in the Jableh sub-district / Al-Musaib project (55 km south of Baghdad), as well as the Biotechnology Laboratory in the College of Agricultural Engineering Sciences / University of Baghdad for the period from 5/1/2022 to 30/10/2022. With the aim of detection the ANXA9 gene polymorphism and its relationship to Daily milk yield (DMY), Lactation period and milk composition, as well as the Polymorphism distribution and allele frequency in 52 Awassi sheep and its lambs, three polymorphism appeared in this variant (T>G SNP) which are TT, TG and GG, and their percentage were 51.92, 40.38 and 7.69%, and the differences between them were highly significant (P≤0.01), with a frequency of 0.72 and 0.28 for the T and G alleles, respectively. the daily milk production rate of Awassi ewes was affected significantly (P≤0.05) by the ANXA9 gene polymorphism, the first variation (T>G SNP), for ewes with the TG polymorphism (1128.65 g), while the components of milk were not affected significantly except for the percentage of Fat, which was maximum in the milk of ewes for GG and TT genotype (5.67 and 5.64%).We can conclude by studying the ANXA9 gene polymorphism that they can be adopted in developing strategies for genetic improvement of sheep, and the application of the study to a larger sample and to several sites and extracting the interaction between two SNPs would give more accurate results and determine the best method for managing and improving sheep flocks.